2005
DOI: 10.1101/gad.1293805
|View full text |Cite
|
Sign up to set email alerts
|

A telomeric repeat sequence adjacent to a DNA double-stranded break produces an anticheckpoint

Abstract: Telomeres are complex structures that serve to protect chromosome ends. Here we provide evidence that in Saccharomyces cerevisiae telomeres may contain an anticheckpoint activity that prevents chromosome ends from signaling cell cycle arrest. We found that an internal tract of telomeric repeats inhibited DNA damage checkpoint signaling from adjacent double-strand breaks (DSBs); cell cycle arrest lasted 8-12 h from a normal DSB, whereas it lasted only 1-2 h from a DSB adjacent to a telomeric repeat. The shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 54 publications
9
75
1
Order By: Relevance
“…DNA double-strand breaks are typically resected, initially being degraded from 59 to 39 to create single-stranded 39 overhangs at the break (White and Haber 1990). However, it has been shown that when short tracts of telomere repeat sequences are placed adjacent to the DNA break site, the broken DNA end is protected from degradation (Diede and Gottschling 1999;Michelson et al 2005;Hirano and Sugimoto 2007). The presence of this telomere ''seed'' sequence also greatly stimulates the addition of new telomere repeats to the DSB (Diede and Gottschling 1999).…”
Section: Resultsmentioning
confidence: 99%
“…DNA double-strand breaks are typically resected, initially being degraded from 59 to 39 to create single-stranded 39 overhangs at the break (White and Haber 1990). However, it has been shown that when short tracts of telomere repeat sequences are placed adjacent to the DNA break site, the broken DNA end is protected from degradation (Diede and Gottschling 1999;Michelson et al 2005;Hirano and Sugimoto 2007). The presence of this telomere ''seed'' sequence also greatly stimulates the addition of new telomere repeats to the DSB (Diede and Gottschling 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In any case, loss of the distal DNA fragment could shut off checkpoint signaling. Recently, Michelson et al (2005) showed that telomeric TG repeat sequence inhibits checkpoint signaling from damage sites, and they proposed a model in which the TG sequence could inhibit checkpoint signaling nearby. In their report, the TG sequence was inserted only into the centromereproximal side of the HO cleavage site that is 20 kb away from the chromosome end.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ATM and ATR family proteins are also required for proper maintenance of telomeres (Greenwell et al, 1995;Metcalfe et al, 1996;Ritchie et al, 1999). Recent evidence suggests that addition of telomeric TG repeats adjacent to DSBs inhibits the activation of checkpoint response in budding yeast (Michelson et al, 2005). However, it is not clear how telomeres control ATR/Mec1 and ATM/Tel1 to inhibit checkpoint responses.…”
mentioning
confidence: 94%
“…Work from the Weinert group, published in this issue of Genes & Development (Michelson et al 2005), provides new insights into this process, by reporting that telomere repeats are able to quench local DNA damage responses, thereby conferring what the authors dub an "anticheckpoint." Their experimental approach exploited a previously developed system to induce de novo telomere formation at a newly created DNA end (Diede and Gottschling 1999): An inducible site-specific endonuclease, called HO, is used to generate a DSB immediately downstream of an internal tract of yeast telomere repeats (Fig.…”
mentioning
confidence: 99%
“…Michelson et al (2005) discovered that although the nontelomeric product of the cleavage reaction (i.e., the end of the distal portion of the chromosome) ( Fig. 1) was still capable of invoking an initial DNA damage response, the extent of this response was affected by the proximity of the DSB to the new telomere.…”
mentioning
confidence: 99%